ASSESSMENT OF COMPETITIVENESS OF MILK PRODUCTION UNDER EXPORT CONDITIONS - S. T. Toleugaliyeva (Экономика: стратегия и практика, 2019)
The problem of increasing the competitiveness of milk and dairy products, raising competition in the market is important for the development of dairy and dairy products of domestic producers. Therefore, it is necessary to increase the competitiveness of dairy products. The aim оf the research is to study the impact of the main factors that contribute to the increase of competitiveness and promotion of milk and dairy products in our country.The study uses quantitative methods of research, ie the method of economic and mathematical modeling using statistical data. Mathematical models are created on the basis of statistical data using numerical methods of research. The article highlights the need to identify the key factors that affect the competitiveness of milk and dairy products in the promotion of export, first of all, in the promotion of export. This issue is especially important in the agricultural sector in the food market, including for dairy companies. This is because agriculture is an important sectorof the country’s economy that provides food for the population.It is necessary to increase milk reserves in our country. For this purpose it is necessary to open milk processing points in the country, and to ensure its logistics, it is planned to purchase milk carriers.The article analyzes and analyzes factors that contribute to the competitiveness of milk production in the country and its export shift.